Efficacy, patient‐reported outcomes and safety profile of ATX‐101 (deoxycholic acid), an injectable drug for the reduction of unwanted submental fat: results from a phase III, randomized, placebo‐controlled study. (8th March 2014) - Ascher, B.; Hoffmann, K.; Walker, P.; Lippert, S.; Wollina, U.; Havlickova, B.
Abstract Background Unwanted submental fat (SMF) may result in an unattractive chin profile and dissatisfaction with appearance. An approved and rigorously tested non‐surgical method for SMF reduction is lacking. Objective To evaluate the efficacy and safety of ATX‐101 for the pharmacological reduction of unwanted SMF in a phase III randomized, double‐blind, placebo‐controlled study. Methods Patients (n = 360) with moderate or severe SMF were randomized to receive ATX‐101 1 or 2 mg/cm2 or placebo injected into their SMF for up to four treatments ~28 days apart, with a 12‐week follow‐up. Coprimary efficacy endpoints were the proportions of treatment responders, defined as a ≥1‐point reduction in SMF on the Clinician‐Reported Submental Fat Rating Scale (CR‐SMFRS), and those satisfied with their appearance in association with their face and chin after treatment on the Subject Self‐Rating Scale (SSRS score ≥4). Secondary efficacy endpoints included a ≥1‐point improvement in SMF on the Patient‐Reported Submental Fat Rating Scale (PR‐SMFRS) and changes in the Patient‐Reported Submental Fat Impact Scale (PR‐SMFIS). Additional patient‐reported outcomes and changes in the Skin Laxity Rating Scale were recorded. Adverse events (AEs) and laboratory test results were monitored. Results Compared with placebo, a greater proportion of patients treated with ATX‐101 1 and 2 mg/cm2 showed a ≥1‐point improvement in CR‐SMFRS (58.3% and 62.3%, respectively, vs. 34.5% with placebo; P < 0.001) and patient satisfaction (SSRS score ≥4) with the appearance of their face and chin (68.3% and 64.8%, respectively, vs. 29.3%; P < 0.001). Patient‐reported secondary efficacy endpoints showed significant improvements in SMF severity (PR‐SMFRS; P = 0.009 for ATX‐101 1 mg/cm2, P < 0.001 for ATX‐101 2 mg/cm2 vs. placebo) and emotions and perceived self‐image (PR‐SMFIS; P < 0.001). No overall worsening of skin laxity was observed. AEs were mostly transient, mild to moderate in intensity and localized to the treatment area. Conclusion ATX‐101 was effective and well tolerated, and may be an alternative to surgery for patients desiring improvement of their submental profile.